Chemical marker identification of mixed essential oil formulation - Sureechatchaiyan P. (2014)
The objective of this study was to identify chemical markers of mixed essential oil formulation from medicinal plants used in herbal compressed ball. The chemical markers serve as standard substances for preliminary quality control of the formulations containing mixed essential oils. In this study, the formulation contained 40.28% plai oil, 5.56% turmeric oil, 1.39% lemongrass oil and 8.33 % kaffir lime oil. All the essential oils used in the formulation were extracted from medicinal plants commonly used in traditional herbal compressed ball. Camphor, borneol and menthol: 13.89%, 8.33% and 22.22%, respectively, were added to the formulation in order to get more aroma and cool feeling when applied onto skin. The chemical components of the formulation were analyzed by gas chromatographic method. The main chemical components that showed sharp and clear peaks on gas chromatogram were sabinene, limonene, camphor and menthol. The correlation between the concentrations of mixed essential oils in the formulation and the detector responses of main chemical components was determined. The correlation coefficients (R2) of sabinene, limonene, camphor and menthol were all higher than 0.995 in the concentration ranging from 0.20%w/v to 2.6%w/v which indicated the linear relationship between the detector responses and the concentrations of the formulation. Therefore, sabinene, limonene, camphor and menthol can be used as the chemical markers of the mixed essential oil formulation from medicinal plants used in herbal compressed ball.